GENERALISASI OPERATOR ⊞_n dan ⊠_n PADA SUBGRUP FUZZY INTUITIONISTIK - Chumaedi Sugihandardji; Ari Wardayani; Dian Pratama (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Intuitionistic fuzzy sets is an extension of the fuzzy set with the characteristics of each element having a degree of membership and non-membership which when added up is less than one. If applied to group theory, it will called intuitionistic fuzzy group. Operators on fuzzy sets associate membership functions (non-membership) with intervals [0,1]. This study examines the general form of operators  and  for   in intuitionistic fuzzy groups. The properties to be studied are the structure of of  and  from an intuitionistic fuzzy group A